Introducing a model for improving the quality of developmental care in the neonatal intensive care unit in Iran - Torkzahrani, Shahnaz; Soleimani, Farin; Rafiey, Hassan; Salavati, Mahyar; Babamahmoodi, Abdolreza (Advances in Nursing & Midwifery, 2016)
Background and Aim Developmental care along with medical care controls premature infant's potential stress. Improving the quality of developmental care as well as other healthcare services is very important. In this paper, the existing quality care improvement models have been reviewed and followed by analysis of their applications to the Iranian NICU. Consequently, an appropriate model is proposed. Materials and Methods In this review article, Iran Medex، Science direct، Google Scholar، SID, PubMed, Scopus, and EBSCOCINAHL databases have been searched by keywords including quality improvement, quality, developmental care, health care, NICU, premature infants. The content of articles were analyzed and compared. Results The review of the literature indicates that there are many health care improvement models. Some of macro and micro related models are applicable in NICUs. However, there are some limitations in this regards. With considering the characteristics of developmental care and the attributes of an ideal health care improvement model a number of models chose to promote developmental care in Iranian's NICU. The models are "Quality Improvement Collaborative", Clinical Pathways, Plan- DO- Study- Act Cycle, Six Sigma, EFQM and ISO. Keywords Developmental care; Neonatal Intensive Care Units; Healthcare; Quality Improvement